Study of Performance of Small Engine Running Continuously Compared to TIS 787-2551 Standards - Khomkaew, Sompot; Suksabai , Nattapong; Kaewpoung, Supachai (Srinakharinwirot University Engineering Journal, 2024)
This research aims to study and compare the performance of a small 4-stroke diesel engine with a newly designed single-cylinder engine with a maximum power of 8.5 kW compared to the TIS.787-2551 continuous operation type. The engine, utilizes B7 diesel fuel and SAE 30-40 lubricating oil. The air filter type is wet and the engine has one piston with a bore of 92 mm, a stroke of 96 mm, and a total displacement volume of 638 cm3. The compression ratio is 19.4:1, and the cooling system is a honeycomb water jacket with a cooling water capacity of 2.09 m3. The engine is designed to operate continuously for 10 hours with an injection pressure of 125 kg/cm2. The intake valve clearance is set at 0.18 mm before top dead center (BTDC) on the opening side and 16.51 degrees BTDC on the closing side. The exhaust valve clearance is set at 0.15 mm before BTDC on the opening side and 50.71 degrees BTDC on the closing side. The testing is conducted under atmospheric pressure conditions starting at 760 mmHg, with a humidity level of 64% at the beginning and 78% after the test. The exhaust smoke color must not exceed 30% according to the Bosch exhaust gas measuring system. The lubricating oil temperature must not exceed 120°C, and the noise level must not exceed 100 dB. After testing, it was found that the tested small engine produced a maximum output power of 7.9 kW, a maximum torque of 31.3 N.m at 2400 rpm, with a fuel consumption rate of 284 g/kWh and exhaust smoke color of 7.2%, reaching a maximum noise level of 93.4 dB.